Peran Massive Open Online Course Terhadap Pembelajaran Al-Quran di Indonesia - MAQBUL, MOH. (Inovasi: Jurnal Diklat Keagamaan, 2020)
The importance of technology in the current era has brought the world of education to issue learning innovations that are ready to meet the demands of the times. Including the existence of open courses based online or commonly called the Massive Open Online Course (MOOC). The platform provided by the world of courses is now widely found, including in Indonesia. In fact, the average organizer does not charge fees for joining the platform . However, the development of this MOOC-based learning did not touch much on the world of Islamic Education, especially the learning of the Qur'an. In addition, this research also touched on the difference between MOOC and Learning Management System (LMS) because there are still many 'same' assumptions regarding MOOC and LMS. Of the two, the discussion will be directed more towards the learning of Islam, especially in the field of Qur'anic science